Differences in the Classroom : Gender, Race, and Trauma as Affective Hotspots in Finnish Education for Adult Migrants - Järvinen, Miitta; Suopajärvi, Tiina (Routledge, 2025)
In this article, we examine the affects that become constructed in Finnish education for adult migrants. Our point of departure for analysing the research material-educators' interviews-is in the everyday situations where educators' and students' emotions and life experiences meet with the institutional conditions of education. In the educators' narrations of these situations, the affects are constructed in patterns attached to intersectional categories of difference. The most affectively intense categories are gender, race, and trauma. With the first two being the classic subjects of feminist analysis and the latter less traditional, we argue that utilizing affect theory can produce new knowledge of these categories and of educators' work. Our analysis shows that, whereas the affective patterns of gender and race become rooted in cultural and structural factors, the pattern of trauma is more difficult to grasp. We also show that understanding the affective patterns of educators' work can disclose how to encounter differences in the classroom.